Responses by Australian auditors to the global financial crisis. (18th December 2011) - Xu, Yang; Carson, Elizabeth; Fargher, Neil; Jiang, Liwei
Abstract: We examine the impact of the global financial crisis (GFC) on auditor behaviour in Australia. Using a sample of listed companies, we examine whether the GFC impacted the propensity of auditors to issue going concern modifications and increased audit effort as reflected in audit fees and audit reporting lag. Controlling for client characteristics, we find an increase in the propensity to issue going concern opinions during the period 2008–2009 compared with the period 2005–2007 and that Big N auditors responded to the GFC earlier than non‐Big N auditors. In relation to audit effort, we find evidence of increased audit fees during the period 2008–2009 compared with the period 2005–2007. There is, however, no evidence of increased audit reporting lags during the GFC.